Independence Analysis of Firing and Rule-based Net Transformations in Reconfigurable Object Nets - Biermann, Enrico; Modica, Tony (Electronic Communications of the EASST, 2008)
The main idea behind Reconfigurable Object Nets (RONs) is to support the visual specification of controlled rule-based net transformations of place/transition nets (P/T nets). RONs are high-level nets with two types of tokens: object nets (place/transition nets) and net transformation rules (a dedicated type of graph transformation rules). Firing of high-level transitions may involve firing of object net transitions, transporting object net tokens through the high-level net, and applying net transformation rules to object nets, e.g. to model net reconfigurations. A visual editor and simulator for RONs has been developed as a plug-in for ECLIPSE using the ECLIPSE Modeling Framework (EMF) and Graphical Editor Framework (GEF) plug-ins. The problem in this context is to analyze under which conditions net transformations and token firing can be executed in arbitrary order. This problem has been solved formally in a previous paper. In this contribution we present an extension of our RON tool which implements the analysis of conflicts between parallel enabled transitions, between parallel applicable net transformation rules (Church-Rosser property), and between transition firing and net transformation steps. The conflict analysis is applied to a RON simulating a distributed producer-consumer system.